2017
DOI: 10.1016/j.ejphar.2017.08.034
|View full text |Cite
|
Sign up to set email alerts
|

14-O-Methylmorphine: A Novel Selective Mu-Opioid Receptor Agonist with High Efficacy and Affinity

Abstract: A B S T R A C T14-O-methyl (14-O-Me) group in morphine-6-O-sulfate (M6SU) or oxymorphone has been reported to be essential for enhanced affinity, potency and antinociceptive effect of these opioids. Herein we report on the pharmacological properties (potency, affinity and efficacy) of the new compound, 14-O-methylmorphine (14-OMeM) in in vitro. Additionally, we also investigated the antinociceptive effect of the novel compound, as well as its inhibitory action on gastrointestinal transit in in vivo. binding. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…Accordingly, 14-OMeC6SU showed the highest affinity for MOR compared to C6SU or codeine and displayed similar binding properties as described in earlier studies, together with codeine [14,17,27]. Our results correspond well with previous data and confirm that the 14-O-methylation of the morphinan structure significantly enhances not only the affinity for MOR, but also for DOR and KOR [4,6,20,22,23]. Other research groups have reported that 14-O-methyl analogs of oxymorphone have improved affinity, agonist activity and antinociceptive potency compared to their parent compound, oxymorphone [36].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Accordingly, 14-OMeC6SU showed the highest affinity for MOR compared to C6SU or codeine and displayed similar binding properties as described in earlier studies, together with codeine [14,17,27]. Our results correspond well with previous data and confirm that the 14-O-methylation of the morphinan structure significantly enhances not only the affinity for MOR, but also for DOR and KOR [4,6,20,22,23]. Other research groups have reported that 14-O-methyl analogs of oxymorphone have improved affinity, agonist activity and antinociceptive potency compared to their parent compound, oxymorphone [36].…”
Section: Discussionsupporting
confidence: 91%
“…The novel codeine analog 14-OMeC6SU, CS6U and the parent compound codeine were tested for opioid receptor binding affinity and selectivity in in vitro radioligand competition binding assays using prototypic selective radioligands for MOR and DOR in rat brain membrane homogenates, or for KOR in guinea pig brain membrane homogenates. The prototypic opioid ligands displayed high affinity as expected and are in accordance with previous data [20,23].…”
Section: Receptor Binding Assayssupporting
confidence: 91%
See 3 more Smart Citations